Environmental tracers to evaluate groundwater residence times and 1 water quality risk in shallow unconfined aquifers in sub Saharan Africa - Banks, Eddie W.; Owor, Michael; Okullo, Joseph; Kebede, Seifu; Makuluni, Patrick; Shaba, Chikondi E.; MacDonald, Alan M. (Journal of Hydrology, 2021)
In sub-Saharan Africa, shallow aquifer systems are relied on as the main safe and secure water resource available to rural communities. Information on the sustainability and vulnerability of groundwater abstraction is becoming increasingly important as groundwater development increases. As part of the UpGro Consortium Project- Hidden Crisis, 150 hand pumped boreholes (HPBs), ranging between 15 and 101 m depth were investigated to examine the resilience of aquifer systems in the Ethiopian Highlands, and the crystalline basement rocks of Uganda and Malawi. Environmental tracers (chlorofluorocarbons (CFCs), SF6, chloride and the stable isotopes of water), water quality indicators (nitrate and E. coli), and groundwater-level time series data were used to estimate groundwater residence time and recharge at a regional scale (100–10,000 km2) and investigate the risks to water quality and water supply over different timeframes, and geological and climatic environments. Average estimated recharge rates using three different techniques (CFCs, chloride mass balance, water table fluctuation method) were between 30 and 330, 27–110 and 30–170 mm y−1, for sites in Ethiopia, Uganda and Malawi, respectively. These estimates of recharge suggests abstraction from dispersed low-yielding HPBs is sustainable. Comparison of stable isotopes in rainfall and groundwater indicates that there is little evaporation prior to recharge, and recharge events are biased to months with greater rainfall and more intense rainfall events There was a weak correlation between nitrate and CFCs within all three countries, and no correlation between E. coli and CFCs within Ethiopia or Malawi. The presence of E. coli at a large proportion of the sites (Ethiopia = 38%, Uganda = 65% and Malawi = 47%) suggests rapid transit of contaminated surface water into the borehole and its presence in groundwater that has CFC-12 concentrations less than 75 pg kg−1 indicates mixing of very young water with water >40 years old. The rapid transit pathways are most likely associated with damaged HPB headworks and poor construction. In several monitored HPBs, daily drawdown due to pumping, drew the groundwater levels close to the base of the HPB, indicating that these HPBs were located in parts of the aquifer with low permeability, or were poorly designed, offering limited capacity for increased demand. Improved HPB siting and construction, coupled with groundwater level monitoring are required to capitalise on the more resilient groundwater within the shallow aquifers and safeguard adequate and good quality water supply for rural communities.
Keywords: sub-Saharan Africa; Environmental tracers; Groundwater recharge; Chloride mass balance; Water quality; Groundwater resilience